Postpartum depression in postpartum 6-month period and effects on the infants - Nazlı Ulusoy, Menekşe; Marakoglu, Kamile (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: To evaluate the risk factors affecting postpartum depression and evaluate the effect of postpartum depression on infant nutrition and growth. Methods: The study was designed as a longitudinal evaluation of mother-infant pairs by repeated measures over six months and surveyed in a Maternity and Children’s Hospital in Karaman, Turkey. Maternal introduction form, Edinburgh Postpartum Depression Scale, Baby Assessment and LATCH Charting System were used on 157 mother-infant pairs during 48 hours, 1st, 3rd and 6th months of delivery. Results: According to this study, from 1st month to 6th month after delivery, 35% women were found to have developed symptomatology of postpartum depression. Of these, 21.7% of women showed the symptoms in the first 48 hours after delivery, 17.2%, 15.3% and 22.3% of women exhibited the synproms at the end of the first, third and sixth month, respectively. About 61.8% women, who were found to have postpartum depression symptomatology in the first 48 hours after delivery, were found to have postpartum depression symptomatology at other control points as well. Frequency of postpartum depression symptomatology, affect having previous depression [OR, 95% CI; 3.452 (1.454-8.191)] (p=.005) and negative relation to spouse [OR, 95% CI; 3.255 (1.039, 10.196)] (p=.043). Conclusions: According to the research results, it should not be forgotten that patients having experienced depression or diagnosed with depression previously and who have postpartum depression symptomatology in first 48 hours, face a major risk of postpartum depression symtomatology. It was recommended that women who have postpartum depression immediately should be offered necessary support, treatment and guidance by cooperation of family physicians and nurses